2013
DOI: 10.1039/c3bm60024f
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced endocytosis of acid-sensitive doxorubicin derivatives with intelligent nanogel for improved security and efficacy

Abstract: The combination of acid-sensitive doxorubicin derivatives with a pH and reduction dual-responsive nanogel exhibited improved chemotherapy security and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 47 publications
1
49
0
1
Order By: Relevance
“…Nanocarriers can be versatile designed to attain passive or active targeting and efficient cellular uptake [4,5]. Components able to recognize stimuli that are unique to certain diseases or pathologies may allow the nanocarrier to release the drug in response to specific pathological triggers [6][7][8]. Unlike pH-sensitive nanocarriers that are intended to release payloads in the mildly acidic extracellular environment of tumors and/ or endo/lysosomal compartments, reduction-sensitive nanocarriers are mostly designed to rapidly dissociate and efficiently release drugs in the cytoplasm and/or cell nucleus [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nanocarriers can be versatile designed to attain passive or active targeting and efficient cellular uptake [4,5]. Components able to recognize stimuli that are unique to certain diseases or pathologies may allow the nanocarrier to release the drug in response to specific pathological triggers [6][7][8]. Unlike pH-sensitive nanocarriers that are intended to release payloads in the mildly acidic extracellular environment of tumors and/ or endo/lysosomal compartments, reduction-sensitive nanocarriers are mostly designed to rapidly dissociate and efficiently release drugs in the cytoplasm and/or cell nucleus [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the micelle with the largest proportion of PCD possessed excellent abilities in drug release, cell internalization as well as proliferation inhibitory effect toward human A549 lung cancer cells. The results demonstrated that the stereocomplex and host-guest interactions-mediated PLA micelles exhibited great potential in sustained drug delivery.In recent years, self-assembled polyester micelles have attracted a great deal of attention in the application for drug delivery, mainly due to its optimal biodegradability and biocompatibility [1,2] . Hydrophilic poly(ethylene glycol) (PEG) and hydrophobic polylactide (PLA) are universally used components in block copolymers, and such copolymers have shown distinctive properties in multiple studies [3,4] .…”
mentioning
confidence: 99%
“…In recent years, self-assembled polyester micelles have attracted a great deal of attention in the application for drug delivery, mainly due to its optimal biodegradability and biocompatibility [1,2] . Hydrophilic poly(ethylene glycol) (PEG) and hydrophobic polylactide (PLA) are universally used components in block copolymers, and such copolymers have shown distinctive properties in multiple studies [3,4] .…”
mentioning
confidence: 99%
“…Reduction-responsive polymeric nanogels for tumor-specific targeting have shown potential for targeted intra-cellular delivery of chemotherapeutic drugs in cancer therapy [48][49][50][51][52][53][54]. Thermo-responsive and pH-responsive polypeptide vesicles revealed a promising approach for smart drug delivery with enhanced efficacy and security [54][55][56][57] demonstrating a prospective future of nanoparticle drug delivery in the disease management.…”
Section: Future Trendsmentioning
confidence: 99%